Evaluation of Maternal and Foetal Outcome in Patients with Incidentally Diagnosed Müllerian Anomaly during Caesarean Section: A Retrospective Descriptive Study - Deepali Raina; Niharika Aggarwal; Geeta Katheit Rai; Anubhuti Singh; Vaishali Vijan (Journal of Clinical and Diagnostic Research)
Introduction: Congenital uterine anomalies, also known as Müllerian anomalies, have an overall prevalence rate of 0.06% to 38%, depending on the type of study population and diagnostic techniques used in various studies. Müllerian anomalies develop due to defective organogenesis of the genital tract. These anomalies can remain asymptomatic or present with a varied range of symptoms, including perinatal, maternal and foetal morbidities. Aim: To study the maternal and foetal outcomes in patients with incidentally diagnosed Müllerian anomalies during caesarean section and to compare the perinatal outcomes with the type of Müllerian anomaly diagnosed. Materials and Methods: A retrospective descriptive study was conducted in the Department of Obstetrics and Gynaecology, School of Medical Sciences and Research, Sharda University, Greater Noida, Uttar Pradesh, India. A retrospective review of the records of all patients who underwent Lower Segment Caesarean Section (LSCS) in the hospital from October 2017 to December 2022 was performed. The patients with intraoperatively documented incidental findings of Müllerian anomalies were selected. Results: The mean age of study participants was 25.6 years. Among a total of 2186 patients, 40 women were found to have Müllerian anomalies intraoperatively, resulting in a prevalence of 1.83%. A septate uterus was present in 14 (35%) patients, making it the most common Müllerian anomaly. Malpresentation was noted in 22 (55%) patients and was the most common indication for caesarean section. Foetal complications, such as preterm birth, were observed in 10 (25%) patients and low birth weight was seen in 15 (37.5%) patients. On a positive note, no baby was born at extremely premature gestation (<28 weeks) and 75% of women were able to carry their pregnancies to term successfully. A total of 80% of the babies born did not require any Neonatal Intensive Care Unit (NICU) and no baby had an extremely low birth weight (<1000 grams). Conclusion: Patients with known Müllerian anomalies can have an acceptable maternal and foetal outcome with vigilant obstetrical care.